Панцирные клещи (Acariformes, Oribatei) целинной степи Приазовья - Ярошенко, Н.Н. (Вестник зоологии, 1975)
Fauna and dynamics of the number of Oribatei (Acariformes) in the virgin steppe of the Azov Sea area («Khomutovskaya Step») were studied in 1969-1971. 95 species be- longing to 40 families were detected. The summer (June) and autumn (November) peaks in the Oribatei number dynamics were determined.